2023
DOI: 10.1302/2633-1462.46.bjo-2023-0044.r1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of suitable outpatient candidates following revision total knee arthroplasty using machine learning

Abstract: AimsTo identify variables independently associated with same-day discharge (SDD) of patients following revision total knee arthroplasty (rTKA) and to develop machine learning algorithms to predict suitable candidates for outpatient rTKA.MethodsData were obtained from the American College of Surgeons National Quality Improvement Programme (ACS-NSQIP) database from the years 2018 to 2020. Patients with elective, unilateral rTKA procedures and a total hospital length of stay between zero and four days were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Many studies on revision TAA report similar constraints, particularly within TAA, 13 but also within other forms of TJA. 4,7,11,16,22,30,33 We used only INBONE II for revision TAA, and although the INBONE II system was not designed specifically for revision TAA, it has been widely used for revision cases.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies on revision TAA report similar constraints, particularly within TAA, 13 but also within other forms of TJA. 4,7,11,16,22,30,33 We used only INBONE II for revision TAA, and although the INBONE II system was not designed specifically for revision TAA, it has been widely used for revision cases.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, anticipating a patient's specific postoperative outcome and clinical trajectory requires simultaneous consideration of several different patient-specific factors. Applications of AI in preoperative evaluation include determining candidacy for surgery and identification of factors associated with achieving meaningful, patient-specific postoperative outcomes 34-60 (Table I), which may currently be the most frequent application of AI within orthopaedics. Because the current value-driven health care system places importance on clinically significant outcome improvements, PROMs serve an important role in the quantification of patient-perceived improvement and therefore help determine the quality of care that patients receive 61-65 .…”
Section: Preoperative Evaluation For Operative Planning and Patient-s...mentioning
confidence: 99%
“…The random-forest model had the best accuracy, and variables of importance were joint-line change, postoperative femorotibial angle, and hemoglobin A1c 64 . Yeramosu et al 65 compared a multivariable logistic regression model and diverse machine learning techniques and found that 1 of the models (random forest) had an accuracy (AUC) of 0.810 for identifying candidates for same-day discharge after revision TKA. According to that model, the factors of importance for same-day discharge, in decreasing order, were operative time, anesthesia type, age, BMI, American Society of Anesthesiologists (ASA) class, race, diabetes, revision TKA type, sex, and smoking.…”
Section: Machine Learning and Artificial Intelligencementioning
confidence: 99%